Operational alteration of the Labor Capacity Index measurement model for qualitative work - Linke, Knut (Advances in Social Sciences Research Journal, 2020)
The Marx term Labour capacity contains the ability to handle change, imponderables and complexity and is personal part of an employee. The Labour Capacity Index (LCI) is developed to measure the use of labour capacity at work places and from employee itself. The index helps to understand the handling and dealing of complexity and imponderables at work. For the index itself is assumed that the index itself news small adjustment to be more valuable. A critic point of the LCI seems to be the existing scale and the used values, do to limitations on the available record set. This paper displays the results of a hopeful useful change in the operationalization of the measurement of labour capacity to increase the understanding of workers and their personal and experienced input to work. The comparison of the results is based on a survey with the working environment of IT employees. From the analysis of the results and out of the following comparison between the new and the old approach for the LCI, it can be displayed that the change in the operationalization can be done successfully. The including of new variable values also allowed a more detailed and distributes view on the labour market and the research labor capacity.